Discovery of 1‐Hydroxypyridine‐2(1H)‐thione‐6‐carboxylic Acid as a First‐in‐Class Low‐Cytotoxic Nanomolar Metallo β‐Lactamase Inhibitor. (22nd May 2017) - Shin, Woo Shik; Bergstrom, Alexander; Bonomo, Robert A.; Crowder, Michael W.; Muthyala, Ramaiah; Sham, Yuk Yin
Abstract: VIM‐2 is one of the most common carbapenem‐hydrolyzing metallo β‐lactamases (MBL) found in many drug‐resistant Gram‐negative bacterial strains. Currently, there is a lack of effective lead compounds with optimal therapeutic potential within our drug development pipeline. Here we report the discovery of 1‐hydroxypyridine‐2(1 H )‐thione‐6‐carboxylic acid (3 ) as a first‐in‐class metallo β‐lactamase inhibitor (MBLi) with a potent inhibition K i of 13 nm against VIM‐2 that corresponds to a remarkable 0.99 ligand efficiency. We further established that3 can restore the antibiotic activity of amoxicillin against VIM‐2‐producing E. coli in a whole cell assay with an EC50 of 110 nm. The potential mode of binding of3 from molecular modeling provided structural insights that could corroborate the observed changes in the biochemical activities. Finally, 3 possesses a low cytotoxicity (CC50 ) of 97 μm with a corresponding therapeutic index of 880, making it a promising lead candidate for further optimization in combination antibacterial therapy. Abstract : An old dog with new tricks ! Pyrithione is a well‐established pharmacophore for zinc‐specific chelation. The discovery of 1‐hydroxypyridine‐2(1 H )‐thione‐6‐carboxylic acid as a first‐in‐class metallo β‐lactamase inhibitor that can rescue β‐lactam antibiotic activity represents a promising lead for further development.